Penanda (Signifier) dan Petanda (Signified) Komodifikasi Seks Dalam Film Kambing Jantan Karya Rudi Soedjarwo - Tri Melia Damaiyanti; Yunindyawati Yunindyawati; Vieronica Varbi Sununianti (Master Program in Sociology, Faculty of Social and Political Science, Universitas Sriwijay, 2016)
This research entitled The Signifier and Signified of Sex Commodification in the Movie Kambing Jantan created by Rudi Soedjarwo. The problems in this research are signifier (form), signified (mean) and signification (interpretation) about sex commodification in this movie Kambing Jantan created by Rudi Soedjarwo. This research was desriptive qualitative research that used discourse analysis with taking ten informants that consist of five boys and five girls of University Sriwijaya’s student that has watched that film. The result of research showed that the signifier (the form of sex behaviour) in this movie Kambing Jantan was holding hand, hugging and kissing. The signified (the mean of sex behaviour) was to described the reality and to showed affection. The significations in this research were; first, the forms of sex behaviour was not suitable to show in this movie because they assumed that mostly the watchers movie was teenagers and they said that teenager will be easy to imitation the scenes of sex behaviour in the movie. Second, they said that the forms of sex behaviour was permitted to showed in this movie because the scenes of that sex behaviour were not often showed in the movie and the scene that unshowed still in normal stage that not till having sex.